(untitled) (Web of Teachers: Inderscience Research, 2025)
In the paper we discuss the types of lecture demonstrations, as well as the requirements for its conducting at the high school physics department. Physical knowledge obtained through the combined use of mathematical analysis and experimental research will be stronger and more durable than the knowledge of mathematicians or experimenters alone. The effectiveness of a physics lecture course is largely determined by the lecture demonstrations that are part of the course. Demonstration experiments improve the quality of the educational process, contribute to a deeper assimilation of theoretical knowledge, and activation of students’ mental activity. A lecture demonstration allows for an introduction to the theory, confirms the conclusions of the theory, and makes it possible to demonstrate the application of the theory in practice.